#TITLE_ALTERNATIVE# - WICAKSONO (NIM 13203071), ARYO
Wireless communication system like WiMAX is susceptible channel compare to another physical channel. Noise factor, interference, and fading make wireless channel getting more data damage. Mechanism of retransmission can deliver back broken data but reduce performance. The ACM technique reduces retransmission with channel coding and adaptive modulation. Channel coding on wireless communication system has characterized to reduce retransmission giving redundancy bits that advance performance. On this final project, channel coding that used is Convolutional coding. Parameter Convolutional coding like constraint length (K), generator matrices, and code rate that influence performance system will be showed through computer simulation using Matlab. Simulation result shows that BER is decrease so data communication can work better. Graphic Eb/No to BER become parameter from this final project that shows differences with uncoded channel on channel AWGN. Besides channel coding, this final project also analysis influence of adaptive modulation to communication link on WiMAX. Modulation level that investigates on this final project is BPSK, QPSK, 16 QAM, and 64 QAM. Simulation result shows that modulation level that used on WiMAX depend on feedback given based on channel condition. Beside that, adaptive modulation also used to appropriate with modulation level scheme to distance between BTS and receiver.